Clinical study of patients with hypertrophic cardiomyopathy - Bairam, Amjad R.; AL-kinani, Alaa A.; AL-haleem, Mahmood R.; Jawhar, Ghazi A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Hypertrophic cardiomyopathy (HCM) is a common genetic cardiovascular disease. Its morphologically divided into asymmetrical septal hypertrophy, symmetrical concentric hypertrophy and apical hypertrophy,and physiologically divided into obstructive HCM and non obstructive HCM according to the left ventricular outflow tract (LVOT) gradient at rest or with provocation. Several factors that increase risk of sudden cardiac death (SCD), the more risk factors a patient has, the greater the chance that the patient is exposed to sudden death and sufficient to warrant consideration for interventional therapy. Objective: The aims of the study are to evaluate the clinical presentations, risk stratification and family screening of patients with HCM. Patients and methods: This cross sectional study was performed in Ibn-Albitar hospital for cardiac surgery. We studied the prevalence of certain variables among seventy three patients with HCM from “June 2010 to April 2012" including the clinical triggers ,electrocardiographic (ECG) changes, ventricular and supraventricular arrhythmia by holter monitoring, morphological and physiological types of HCM by echocardiography, family screening and finally we assessed the risk factors for SCD and candidacy for interventional procedures. Results: A total of seventy three patients, males to females ratio were 1.5:1 with a mean age of 34±26 (years). HCM was higher in patients younger than 45 years of age, 43(58.9%). Eighty seven percent were symptomatic and (12.3%) were asymptomatic diagnosed by family screening of first degree relatives with HCM. Family history of HCM was identified in (38.3%).Three quarter of patients had asymmetrical septal hypertrophy and (6.8%) had pure apical HCM. Abnormal ECG was found in(87.6%) mainly in the form of left ventricular hypertrophy( LVH )while 9 patients(12.3%) had normal ECG. Nonsustained ventricular tachycardia(NSVT) was found in(30.1%). Echocardiographically, systolic anterior motion(SAM) of the anterior mitral leaflet was seen in about half of patients and three patients (7.6%) had SAM without LVOT obstruction. About half of patients (49.4%) had resting and provocable LVOT obstruction and about half of obstructive type (47.2%) had LVOT gradient ≥50mmhg and are candidate for surgical or percutaneous intervention. Conclusions: Most of our patients were symptomatic and significant number of patients had family history of HCM. Asymmetrical septal hypertrophy was the commonest morphological type of HCM. Relatively equal prevalence of obstructive and nonobstructive HCM and significant number of patients with the obstructive type had LVOT gradient ≥ 50mmhg who are candidate for surgical or trascatheter interventions.